Implementation of Democratic Values in Determining the Political Direction of State Law Regarding General Elections in Indonesia - Zaman, Nurus (Law Research Review Quarterly, 2018)
In this study, there are 2 (two) problems that were examined, namely: First, whether the general election system in Indonesia has adopted values in a real democratic system. Second, what is the formulation for the adoption of democratic system values in the political law of the state regarding general elections. The results of the research can show: First, in determining the direction of political law regarding elections, the concept of democracy adopted by Indonesia uses Pancasila as the main guideline. Because the values in a real democratic system do not stop with the people who determine the leaders and policies of the country, but also in the context of democracy they contain a wider value than that. Second, as a state that adopts a civil law system, the political formulation of general election law is carried out by normalizing the basic law, namely the 1945 Constitution of the Republic of Indonesia and other laws and regulations.